2021
DOI: 10.1002/jcp.30583
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed miRNAs in bone after methotrexate treatment

Abstract: Previous studies have shown that administration of antimetabolite methotrexate (MTX) caused a reduced trabecular bone volume and increased marrow adiposity (bone/fat switch), for which the underlying molecular mechanisms and recovery potential are unclear. Altered expression of microRNAs (miRNAs) has been shown to be associated with dysregulation of osteogenic and/or adipogenic differentiation by disrupting target gene expression. First, the current study confirmed the bone/fat switch following MTX treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Using a rat acute MTX treatment model, previous studies have shown that administration of MTX caused a reduced trabecular bone volume and an increased marrow adiposity [ 30 , 31 , 32 ]. Our recent investigation also confirmed the MTX-induced reduced osteogenesis/increased adipogenesis in vitro [ 24 ]. Consistent with these previous observations, using MC3T3.E1 preosteoblastic cells and 3T3 F442A preadipocytic cells, the current study also observed the reduced osteogenic differentiation and increased adipogenic differentiation following MTX treatment from the precursor cells.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Using a rat acute MTX treatment model, previous studies have shown that administration of MTX caused a reduced trabecular bone volume and an increased marrow adiposity [ 30 , 31 , 32 ]. Our recent investigation also confirmed the MTX-induced reduced osteogenesis/increased adipogenesis in vitro [ 24 ]. Consistent with these previous observations, using MC3T3.E1 preosteoblastic cells and 3T3 F442A preadipocytic cells, the current study also observed the reduced osteogenic differentiation and increased adipogenic differentiation following MTX treatment from the precursor cells.…”
Section: Discussionsupporting
confidence: 74%
“…In both patients and animal models, reduced bone formation and increased marrow adiposity have been observed, and yet the underlying mechanisms are unclear [ 3 , 4 , 13 , 14 ]. Previously, using a rat MTX intense treatment model (five daily injections, mimicking intensive MTX treatment for childhood leukemia), our investigations have identified five upregulated miRNA candidates, namely, miR-155-5p, miR-154-5p, miR-344g, miR-6215, and miR-6315, as promising candidates associated with MTX-induced bone defects [ 24 ]. Based on bioinformatic analyses, among them, miR-6315 was indicated as a potentially important factor involved in bone/bone marrow fat formation defects following MTX treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations